A Study on Android Application Development - Rajkumar A. Soni (Universitas Islam Sultan Agung, 2013)
As and when the world moves towards the hand-held devices, there should be an innovation as well as awareness of such kind of application development used for the hand-held device. As time elapses the world started moves on the fingers using such kind of developed applications. In this paper we discuss the most fundamental attributes and crucial steps followed to create a robust application using Android OS. This kind of contribution will help a lot to the initiators who want to switch-over from other technologies to the mobile application development.